Join the IDNLearn.com community and get your questions answered by knowledgeable individuals. Discover comprehensive answers to your questions from our community of knowledgeable experts.
Sagot :
Certainly! Let's solve the given differential equations step-by-step.
### Part (a)
To solve the differential equation
[tex]\[ \left(x^2 + xy\right) \frac{dy}{dx} = xy + y^2, \][/tex]
we can start by rewriting it in the form:
[tex]\[ (x^2 + xy) \frac{dy}{dx} = y(x + y). \][/tex]
To solve it, we divide both sides by [tex]\(y(x+y)\)[/tex]:
[tex]\[ \frac{(x^2 + xy)}{y(x+y)} \frac{dy}{dx} = 1. \][/tex]
Simplify the left-hand side:
[tex]\[ \frac{x(x + y)}{y(x + y)} \frac{dy}{dx} = 1. \][/tex]
This simplifies to:
[tex]\[ \frac{x}{y} \frac{dy}{dx} = 1. \][/tex]
Now rearrange it to separate the variables:
[tex]\[ \frac{dy}{y} = \frac{dx}{x}. \][/tex]
Integrate both sides:
[tex]\[ \int \frac{1}{y} \, dy = \int \frac{1}{x} \, dx, \][/tex]
which results in:
[tex]\[ \ln|y| = \ln|x| + C, \][/tex]
where [tex]\(C\)[/tex] is the constant of integration.
Exponentiate both sides:
[tex]\[ y = Cx, \][/tex]
where [tex]\(C\)[/tex] can be represented as [tex]\(C_1 = e^C\)[/tex]. Thus, the general solution to the differential equation is:
[tex]\[ y = C_1 x. \][/tex]
This is the solution to part (a).
### Part (b)
To solve the differential equation
[tex]\[ \frac{d^2 y}{dx^2} - 9y = 7e^{5x}, \][/tex]
with initial conditions [tex]\(y(0) = 2\)[/tex] and [tex]\(\frac{dy}{dx}\bigg|_{x=0} = 3\)[/tex], we need to find the general solution to the non-homogeneous differential equation.
First, find the complementary (homogeneous) solution. Consider the homogeneous equation:
[tex]\[ \frac{d^2 y}{dx^2} - 9y = 0. \][/tex]
Assume a solution of the form [tex]\(y = e^{rx}\)[/tex] and substitute it into the differential equation:
[tex]\[ r^2 e^{rx} - 9 e^{rx} = 0. \][/tex]
Factor out [tex]\(e^{rx}\)[/tex]:
[tex]\[ (r^2 - 9)e^{rx} = 0. \][/tex]
This gives us the characteristic equation:
[tex]\[ r^2 - 9 = 0, \][/tex]
[tex]\[ r^2 = 9, \][/tex]
[tex]\[ r = \pm 3. \][/tex]
So, the complementary (homogeneous) solution is:
[tex]\[ y_h = C_1 e^{3x} + C_2 e^{-3x}. \][/tex]
Next, find a particular solution to the non-homogeneous differential equation. We use the method of undetermined coefficients. Assume a particular solution of the form:
[tex]\[ y_p = A e^{5x}. \][/tex]
Substitute [tex]\(y_p\)[/tex] into the non-homogeneous differential equation:
[tex]\[ \frac{d^2}{dx^2} (Ae^{5x}) - 9(Ae^{5x}) = 7e^{5x}, \][/tex]
[tex]\[ 25Ae^{5x} - 9Ae^{5x} = 7e^{5x}, \][/tex]
[tex]\[ (25A - 9A)e^{5x} = 7e^{5x}, \][/tex]
[tex]\[ 16A e^{5x} = 7e^{5x}, \][/tex]
[tex]\[ A = \frac{7}{16}. \][/tex]
Thus, the particular solution is:
[tex]\[ y_p = \frac{7}{16} e^{5x}. \][/tex]
Now, combine the complementary solution and the particular solution:
[tex]\[ y = y_h + y_p, \][/tex]
[tex]\[ y = C_1 e^{3x} + C_2 e^{-3x} + \frac{7}{16} e^{5x}. \][/tex]
Use the initial conditions to find [tex]\(C_1\)[/tex] and [tex]\(C_2\)[/tex]. For [tex]\(y(0) = 2\)[/tex]:
[tex]\[ 2 = C_1 e^{0} + C_2 e^{0} + \frac{7}{16} e^{0}, \][/tex]
[tex]\[ 2 = C_1 + C_2 + \frac{7}{16}, \][/tex]
[tex]\[ C_1 + C_2 = 2 - \frac{7}{16}, \][/tex]
[tex]\[ C_1 + C_2 = \frac{32}{16} - \frac{7}{16}, \][/tex]
[tex]\[ C_1 + C_2 = \frac{25}{16}. \][/tex]
For [tex]\(\frac{dy}{dx}\bigg|_{x=0} = 3\)[/tex]:
[tex]\[ \frac{dy}{dx} = 3C_1 e^{3x} - 3C_2 e^{-3x} + \frac{35}{16} e^{5x}, \][/tex]
[tex]\[ \frac{dy}{dx}\bigg|_{x=0} = 3C_1 - 3C_2 + \frac{35}{16}, \][/tex]
[tex]\[ 3 = 3C_1 - 3C_2 + \frac{35}{16}, \][/tex]
[tex]\[ 3C_1 - 3C_2 = 3 - \frac{35}{16}, \][/tex]
[tex]\[ 3C_1 - 3C_2 = \frac{48}{16} - \frac{35}{16}, \][/tex]
[tex]\[ 3C_1 - 3C_2 = \frac{13}{16}. \][/tex]
Divide both equations by 3:
[tex]\[ C_1 - C_2 = \frac{13}{48}. \][/tex]
Now solve the system of linear equations:
[tex]\[ C_1 + C_2 = \frac{25}{16}, \][/tex]
[tex]\[ C_1 - C_2 = \frac{13}{48}. \][/tex]
Add the two equations:
[tex]\[ 2C_1 = \frac{25}{16} + \frac{13}{48}, \][/tex]
[tex]\[ 2C_1 = \frac{75}{48} + \frac{13}{48}, \][/tex]
[tex]\[ 2C_1 = \frac{88}{48}, \][/tex]
[tex]\[ C_1 = \frac{44}{48}, \][/tex]
[tex]\[ C_1 = \frac{11}{12}. \][/tex]
Subtract the second equation from the first:
[tex]\[ 2C_2 = \frac{25}{16} - \frac{13}{48}, \][/tex]
[tex]\[ 2C_2 = \frac{75}{48} - \frac{13}{48}, \][/tex]
[tex]\[ 2C_2 = \frac{62}{48}, \][/tex]
[tex]\[ C_2 = \frac{31}{48}. \][/tex]
So, the particular solution with initial conditions is:
[tex]\[ y = \frac{7}{16} e^{5x} + \frac{11}{12} e^{3x} + \frac{31}{48} e^{-3x}. \][/tex]
Therefore, the solution to part (b) is:
[tex]\[ y = \frac{7}{16}e^{5x} + \frac{11}{12}e^{3x} + \frac{31}{48}e^{-3x}. \][/tex]
### Final Answer
Our complete solutions are:
- Part (a): [tex]\( y(x) = C_1 x \)[/tex],
- Part (b): [tex]\( y(x) = \frac{7}{16}e^{5x} + \frac{11}{12}e^{3x} + \frac{31}{48}e^{-3x} \)[/tex].
### Part (a)
To solve the differential equation
[tex]\[ \left(x^2 + xy\right) \frac{dy}{dx} = xy + y^2, \][/tex]
we can start by rewriting it in the form:
[tex]\[ (x^2 + xy) \frac{dy}{dx} = y(x + y). \][/tex]
To solve it, we divide both sides by [tex]\(y(x+y)\)[/tex]:
[tex]\[ \frac{(x^2 + xy)}{y(x+y)} \frac{dy}{dx} = 1. \][/tex]
Simplify the left-hand side:
[tex]\[ \frac{x(x + y)}{y(x + y)} \frac{dy}{dx} = 1. \][/tex]
This simplifies to:
[tex]\[ \frac{x}{y} \frac{dy}{dx} = 1. \][/tex]
Now rearrange it to separate the variables:
[tex]\[ \frac{dy}{y} = \frac{dx}{x}. \][/tex]
Integrate both sides:
[tex]\[ \int \frac{1}{y} \, dy = \int \frac{1}{x} \, dx, \][/tex]
which results in:
[tex]\[ \ln|y| = \ln|x| + C, \][/tex]
where [tex]\(C\)[/tex] is the constant of integration.
Exponentiate both sides:
[tex]\[ y = Cx, \][/tex]
where [tex]\(C\)[/tex] can be represented as [tex]\(C_1 = e^C\)[/tex]. Thus, the general solution to the differential equation is:
[tex]\[ y = C_1 x. \][/tex]
This is the solution to part (a).
### Part (b)
To solve the differential equation
[tex]\[ \frac{d^2 y}{dx^2} - 9y = 7e^{5x}, \][/tex]
with initial conditions [tex]\(y(0) = 2\)[/tex] and [tex]\(\frac{dy}{dx}\bigg|_{x=0} = 3\)[/tex], we need to find the general solution to the non-homogeneous differential equation.
First, find the complementary (homogeneous) solution. Consider the homogeneous equation:
[tex]\[ \frac{d^2 y}{dx^2} - 9y = 0. \][/tex]
Assume a solution of the form [tex]\(y = e^{rx}\)[/tex] and substitute it into the differential equation:
[tex]\[ r^2 e^{rx} - 9 e^{rx} = 0. \][/tex]
Factor out [tex]\(e^{rx}\)[/tex]:
[tex]\[ (r^2 - 9)e^{rx} = 0. \][/tex]
This gives us the characteristic equation:
[tex]\[ r^2 - 9 = 0, \][/tex]
[tex]\[ r^2 = 9, \][/tex]
[tex]\[ r = \pm 3. \][/tex]
So, the complementary (homogeneous) solution is:
[tex]\[ y_h = C_1 e^{3x} + C_2 e^{-3x}. \][/tex]
Next, find a particular solution to the non-homogeneous differential equation. We use the method of undetermined coefficients. Assume a particular solution of the form:
[tex]\[ y_p = A e^{5x}. \][/tex]
Substitute [tex]\(y_p\)[/tex] into the non-homogeneous differential equation:
[tex]\[ \frac{d^2}{dx^2} (Ae^{5x}) - 9(Ae^{5x}) = 7e^{5x}, \][/tex]
[tex]\[ 25Ae^{5x} - 9Ae^{5x} = 7e^{5x}, \][/tex]
[tex]\[ (25A - 9A)e^{5x} = 7e^{5x}, \][/tex]
[tex]\[ 16A e^{5x} = 7e^{5x}, \][/tex]
[tex]\[ A = \frac{7}{16}. \][/tex]
Thus, the particular solution is:
[tex]\[ y_p = \frac{7}{16} e^{5x}. \][/tex]
Now, combine the complementary solution and the particular solution:
[tex]\[ y = y_h + y_p, \][/tex]
[tex]\[ y = C_1 e^{3x} + C_2 e^{-3x} + \frac{7}{16} e^{5x}. \][/tex]
Use the initial conditions to find [tex]\(C_1\)[/tex] and [tex]\(C_2\)[/tex]. For [tex]\(y(0) = 2\)[/tex]:
[tex]\[ 2 = C_1 e^{0} + C_2 e^{0} + \frac{7}{16} e^{0}, \][/tex]
[tex]\[ 2 = C_1 + C_2 + \frac{7}{16}, \][/tex]
[tex]\[ C_1 + C_2 = 2 - \frac{7}{16}, \][/tex]
[tex]\[ C_1 + C_2 = \frac{32}{16} - \frac{7}{16}, \][/tex]
[tex]\[ C_1 + C_2 = \frac{25}{16}. \][/tex]
For [tex]\(\frac{dy}{dx}\bigg|_{x=0} = 3\)[/tex]:
[tex]\[ \frac{dy}{dx} = 3C_1 e^{3x} - 3C_2 e^{-3x} + \frac{35}{16} e^{5x}, \][/tex]
[tex]\[ \frac{dy}{dx}\bigg|_{x=0} = 3C_1 - 3C_2 + \frac{35}{16}, \][/tex]
[tex]\[ 3 = 3C_1 - 3C_2 + \frac{35}{16}, \][/tex]
[tex]\[ 3C_1 - 3C_2 = 3 - \frac{35}{16}, \][/tex]
[tex]\[ 3C_1 - 3C_2 = \frac{48}{16} - \frac{35}{16}, \][/tex]
[tex]\[ 3C_1 - 3C_2 = \frac{13}{16}. \][/tex]
Divide both equations by 3:
[tex]\[ C_1 - C_2 = \frac{13}{48}. \][/tex]
Now solve the system of linear equations:
[tex]\[ C_1 + C_2 = \frac{25}{16}, \][/tex]
[tex]\[ C_1 - C_2 = \frac{13}{48}. \][/tex]
Add the two equations:
[tex]\[ 2C_1 = \frac{25}{16} + \frac{13}{48}, \][/tex]
[tex]\[ 2C_1 = \frac{75}{48} + \frac{13}{48}, \][/tex]
[tex]\[ 2C_1 = \frac{88}{48}, \][/tex]
[tex]\[ C_1 = \frac{44}{48}, \][/tex]
[tex]\[ C_1 = \frac{11}{12}. \][/tex]
Subtract the second equation from the first:
[tex]\[ 2C_2 = \frac{25}{16} - \frac{13}{48}, \][/tex]
[tex]\[ 2C_2 = \frac{75}{48} - \frac{13}{48}, \][/tex]
[tex]\[ 2C_2 = \frac{62}{48}, \][/tex]
[tex]\[ C_2 = \frac{31}{48}. \][/tex]
So, the particular solution with initial conditions is:
[tex]\[ y = \frac{7}{16} e^{5x} + \frac{11}{12} e^{3x} + \frac{31}{48} e^{-3x}. \][/tex]
Therefore, the solution to part (b) is:
[tex]\[ y = \frac{7}{16}e^{5x} + \frac{11}{12}e^{3x} + \frac{31}{48}e^{-3x}. \][/tex]
### Final Answer
Our complete solutions are:
- Part (a): [tex]\( y(x) = C_1 x \)[/tex],
- Part (b): [tex]\( y(x) = \frac{7}{16}e^{5x} + \frac{11}{12}e^{3x} + \frac{31}{48}e^{-3x} \)[/tex].
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Find the answers you need at IDNLearn.com. Thanks for stopping by, and come back soon for more valuable insights.